Effect of putrescine on growth and productivity of wheat under water stress conditions - Meena, Pinkey; Solanki, N.S.; L.N. Dashora, L.N. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Rajasthan College of Agriculture, Udaipur, Rajasthan duringrabi 2013-14 to assess the effect of putrescine in mitigating the water stress in wheat. The experimentconsisted of 4 water stress conditions (no water stress, water stress at tillering stage, heading stageand both tillering + heading stage ) and 4 rates of putrescine spray viz., control (water spray), 10ppm, 50 ppm and 100 ppm. Treatments were evaluated using split-plot design allocating waterstress treatments in main- plots and foliar spray of putrescine in sub-plots with four replication.Water stress at tillering, heading and tillering + heading stages caused significant reduction ingrain yield, the magnitude of reduction being 4.0, 11.3 and 16.8 %, respectively over no water stress.No water stress treatment recorded the highest net returns (` 91484ha-1) and B:C ratio (3.1). Prolinecontent increased while Relative Water Content (RWC) and chlorophyll content decreased underwater stress treatments as compared to no water stress treatments. Foliar spray of putrescine 50ppm resulted in significantly higher grain (5712 kg ha-1), straw (8672 kg ha-1) and biological (14384kg ha-1) yields that were found at par with foliar spray of 100 ppm putrescine. Foliar spray ofputrescine fetched lower net returns and B:C ratio as compared to water spray. However, foliarspray of 50 ppm and 100 ppm putrescine significantly increased proline content, RWC, chlorophyllcontent, over foliar spray of putrescine 10 ppm and water spray.